Innovation and firm growth over the business cycle - Andrin Spescha; Martin Woerter (ETH Zurich, KOF Swiss Economic Institute, 2016)
This paper investigates how the macroeconomic business cycle impacts the empirical relation between firms' innovations and their sales growth rates. Based on firm-level panel data over the time period 1995-2014, the paper finds no visible sales growth differentials between firms in booming economic environments. In the economically difficult times of recessions, by contrast, innovative firms show significantly higher sales growth rates than non-innovative firms. This finding is in line with Schumpeter's (1939) business cycle theory, where recessions play an important role in the adaptation of the economy towards innovative products and processes. Moreover, the paper shows that small innovative firms, profiting from their higher organizational flexibility and stronger entrepreneurial commitment, are the main beneficiaries in this adaption process.
Keywords: O33; 330; Innovation; Firm growth; Business cycle; Firm size